Pengaruh Komposisi Matriks Gypsum Berserat Limbah Masker Medis Terhadap Kemampuan Bending - Sitorus, Edo Andreas; Suardana, Ngakan Putu Gede; Kencanawati, Cok Istri Putri Kusuma (Teknik Desain Mekanika, 2022)
Abstract Wasted medical infectious Becomes the problems during the Covid-19 pandemic. Occur enhancement until with 30% while capacity processing still limited. One of is them medical mask waste, becomes conflict for several because how many wasteed masks are thrown away reckless and result in pollution environment around. This research used gypsum as matrix and waste medical masks sterilized as well as chopped sized + 1cm 2 as reinforcement with variation fraction volume 0 % ,5%, 10%, and 15% medical mask waste , manufactured with hand lay up method implanted using an acrylic mold with disordered oriented reinforcement. Composite cut in accordance ASTM D790, tested looking stress, strain, and modulus of elasticity. Bending test data experienced decrease , where highest stress obtained in the 0% fraction of medical mask waste with the average value is 5,448 MPa while the lowest is obtained in the 15% fraction of medical mask waste with the average is 0.842 MPa, the bending strain has enhancement where strain highest obtained in the 10% fraction of medical mask waste with the average value is 0.695%, while the lowest is obtained in the 0% fraction of medical mask waste with average value 0.103%, modulus of elasticity experience decrease , where the modulus of elasticity highest obtained in the 0% fraction of medical mask waste with the average value is 6472.858 MPa, while the lowest obtained in the 15% fraction of medical mask waste with the average value is 261.144 MPa. Keywords: Gypsum, medical mask waste, volume fraction, bending strength